Die Abrahamvertelling as kontranarratief (Afrikaans) - Breytenbach, A.P.B. (Andries Petrus Bernardus), 1944- (University of Pretoria, 2013)
Dissertation (MTh (Old Testament Studies))--University of Pretoria, 2006.